Język a współdziałanie - Łukaszyński, Janusz (The Language and the Co-Operation, 2008)
The article presents a different way of understanding the notion of co-operation. Ali of the concepts discussed in the paper put on the language. The development of the concept of co-operation runs from forms in which the language was only a necessary condition of the co-operation to forms in which linguistic communication itself can be interpreted in categories of co-operation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 13-30